Penerapan Model Pembelajaran Kooperatif untuk Meningkatkan Hasil Belajar dan Aktivitas Siswa Sekolah Dasar - Suwardi, Suwardi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This study is a classroom action research that aims to describe the improvement of learning outcomes and activities of students of class V Elementary School 3 Komet Banjarbaru City on learning materials of water by using cooperative learning model. The subjects of this study are students of grade V Elementary School 3 Komet Banjarbaru City in the academic year 2016/2017 which amounted to 24 people. This study consists of 2 cycles with 2 meetings each cycle. Cycle 1 deals with water evaporation and water condensation and cycle 2 deals with melting and freezing water. The study was conducted for 6 months. The results of cognitive learning are obtained through pretest and posttest, character traits and social skills derived from observations during the learning process, as well as student activity obtained through observation during learning. Data were analyzed descriptively. The results showed that the classical learning completeness increased from cycle 1 to cycle 2 ie from 45.83% to 94%. Character behaviors and social skills increase from cycle 1 to cycle 2 of the category good enough to be good. Student activity has been well evenly in cycle 1 and cycle 2.